2021
DOI: 10.1136/jech-2021-216772
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to ambient fine particulate matter originating from traffic and residential wood combustion and the prevalence of depression

Abstract: IntroductionAir pollution has been suggested to be associated with depression. However, current evidence is conflicting, and no study has considered different sources of ambient particulate matter with an aerodynamic diameter below 2.5 µm (PM2.5). We evaluated the associations of long-term exposure to PM2.5 from road traffic and residential wood combustion with the prevalence of depression in the Helsinki region, Finland.MethodsWe conducted a cross-sectional analysis based on the Helsinki Capital Region Enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…The discrepancies between the cross-sectional and longitudinal results in this study suggest the need for a more critical and in-depth analysis of the links between PM 2.5 exposure and depression, as has been pointed out by other researchers in this field [26,71,72]. The study findings also suggest that reductions in PM 2.5 levels over time may reduce the strength of the association between PM 2.5 exposure and depression in some cases.…”
contrasting
confidence: 57%
“…The discrepancies between the cross-sectional and longitudinal results in this study suggest the need for a more critical and in-depth analysis of the links between PM 2.5 exposure and depression, as has been pointed out by other researchers in this field [26,71,72]. The study findings also suggest that reductions in PM 2.5 levels over time may reduce the strength of the association between PM 2.5 exposure and depression in some cases.…”
contrasting
confidence: 57%
“…Additionally, 2021 saw further interest in whether the source of air pollutants associated with depressive outcomes mattered in the context of better targeting clean air interventions. Examining household air pollutants large Chinese cohort [39,40], and cross-sectional [41] studies, demonstrated positive associations, and of a handful of cross-sectional studies in other settings some replicated these findings [42,43], with others examining specific elements of biomass-burning including black carbon [44] and bushfire smoke [45].…”
Section: Epidemiological Associations Between Air Pollutants and Ment...mentioning
confidence: 88%
“…The results of previous studies are inconsistent on the relationship between household solid fuels use and depressive symptoms [11,27,28,43,44]. Possible reasons for the inconsistent ndings on the association between depression and solid fuels maybe they have different methods to identify depression [45,46], different research subjects and different sample sizes.…”
Section: The Association Between Ses and Household Solid Fuelsmentioning
confidence: 99%
“…Another survey of a total of 4,585 older adults in rural China also showed that those who used solid fuels for cooking were nearly 1.2 times more likely to suffer from depression than those who used clean fuels for cooking [26]. In contrast, a study in the Helsinki region, Finland found no convincing evidence of the effect of long-term exposure to PM2.5 from residential wood combustion on depression [27]. Four European general population cohorts of 70,928 individuals also found no clear evidence for the relationship between air pollution and depressive symptoms [28].…”
mentioning
confidence: 99%